Early-career general practitioners' career intentions in Estonia : A qualitative study - Velgan, Marta; Uibu, Anett; Õunap, Elinor; Kangasniemi, Mari Katariina; Michels, Nele R.; Kalda, Ruth (Taylor & Francis, 2025)
Background: The shortage of general practitioners (GPs) is a worsening problem in many countries and poses a threat to the services provided by primary care and by extension for the entire healthcare system. Issues with GP workforce recruitment and retention can be reasons for this shortage.
Objectives: To describe GP trainees and newly qualified GPs experiences and perceptions on how their training and early experiences of work influence their career intentions in primary care in Estonia.
Methods: A qualitative study with GP trainees (n = 12) and newly qualified GPs (n = 13) using semi-structured group interviews (n = 6) was conducted. Interviews were conducted from October until November 2020. Data were analysed using thematic analysis with NVivo Software.
Results: Although early-career GPs in Estonia envision their future roles as GP practice owners with patient list, this is often postponed due to various reasons. Early-career GPs expressed a sense of unpreparedness to fill all the roles of GPs' and found the process of establishing a GP practice and taking on a patient lists very complicated. They value work-life balance and prefer workplaces, which offer flexible working conditions.
Conclusion: Potential strategies were identified to enhance the willingness of early-career GPs to continue their career as GP practice owners with patient list: improving the GP training program by placing more emphasis on managing skills and making the process of establishing GP practice and taking on a patient list less bureaucratic and more accessible.